A comprehensive analysis of HR operational activities and employee engagement activities of Banglalink - Akanda, Nusrat Jerin (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.